Effects of Public Private Partnerships in Strengthening Faith-Based Health Systems in Kisii County, Kenya - Ringera, William; Tenambergen, Wanja; Oluoch, Musa (International Journal of Professional Practice, 2021)
Public-Private Partnerships (PPPs) are important in enhancement of efficiency and effectiveness in different agencies. PPPs is a concept that has been borrowed and applied in various sectors. It is noted that within governments, Health Ministries’ focus on the public sector often disregard the frequently much larger private finance and private provision of healthcare. This study examined the effects of PPPs in material support, leadership/management, and human resources for health (HRH) on strengthening of health systems in faith-based organization (FBO) health services in Kisii County, Kenya. A cross-sectional descriptive study was conducted targeting 78 FBO facilities’ officials from Tabaka, Christianmarian and Nyanchwa; and officials from the Ministry of Health. Data was collected using structured questionnaires and interview schedules, and analysed using SPSS Version 20 and Ms. Excel. The study found that PPP on leadership and management, material support, HRH and provision of guidelines for the implementation of the PPP were significantly associated with strengthening of FBO health systems at p<0.05.The study conclude that PPPs targeting material support, leadership and management, provision of guidelines for PPP process, and HRH improved provision of public health services in FBO facilities in Kisii County. Therefore, the PPP is yielding fruits in the Government’s effort to strengthen delivery of public health services, particularly in areas of HIV/AIDS and maternal, neonatal and child health-MNCH, in Kisii County. From the viewpoint of Kisii County Government, FBO facilities are able to effectively complement the work of government in public health services and should be supported through the PPPs.